2021
DOI: 10.3390/ijerph18042085
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Hypertension and Fasting Blood Glucose from Real-World Data: Retrospective Cohort for 7-Years Follow-Up

Abstract: This retrospective cohort study was done to investigate the incidence of hypertension and its relation to the fasting blood glucose level in Korea. The eligible non-hypertensive subjects (n = 3,396,187) among the National Health Insurance Service-National Health Screening (NHIS-HEALS) examinees (n = 10,644,911) in 2009 were followed up until 2015. A Cox proportional hazards regression was used to estimate the risk of the high blood glucose level for the incident hypertension while controlling for covariates’ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…To our knowledge, this study is the first to find effect modification of age for the risk of incident hypertension associated with IFG or IGT, showing an increased risk in young/middle-aged participants but not the elderly. While most ( 13 , 14 , 46 48 ) but not all previous studies ( 15 , 49 , 50 ) found that intermediate hyperglycemia burden confers a higher risk of incident hypertension, no study found a significant difference among age groups regarding this risk ( 50 52 ). Sasaki et al ( 53 ) found that among 2,136 and 3,426 Japanese people aged < 65 and ≥65 years, respectively, only middle-aged participants with prediabetes (as defined by IFG or IGT) had an elevated risk for hypertension; however, among middle-aged participants, in the multivariable model, IGT showed a signal of increased risk of hypertension [OR (95% CI): 1.29 (0.98 to 1.70), p -value =0.07].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…To our knowledge, this study is the first to find effect modification of age for the risk of incident hypertension associated with IFG or IGT, showing an increased risk in young/middle-aged participants but not the elderly. While most ( 13 , 14 , 46 48 ) but not all previous studies ( 15 , 49 , 50 ) found that intermediate hyperglycemia burden confers a higher risk of incident hypertension, no study found a significant difference among age groups regarding this risk ( 50 52 ). Sasaki et al ( 53 ) found that among 2,136 and 3,426 Japanese people aged < 65 and ≥65 years, respectively, only middle-aged participants with prediabetes (as defined by IFG or IGT) had an elevated risk for hypertension; however, among middle-aged participants, in the multivariable model, IGT showed a signal of increased risk of hypertension [OR (95% CI): 1.29 (0.98 to 1.70), p -value =0.07].…”
Section: Discussionmentioning
confidence: 84%
“…As reported by ADA, Metformin intervention is as effective as lifestyle changes, especially among the younger population aged 25-44 years (44,45). In the review article by Herman.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[ 30 ] IR can lead to hyperinsulinemia, and result in increased lipid content in vascular smooth muscle cells and fibroblasts. [ 31 ] Second, IR can release inflammatory factors, damage vascular endothelial cells, reduce arterial elasticity, then cause the increase of arterial wall stiffness. [ 32 , 33 ] Taharboucht S. et al [ 34 ] compared 213 NAFLD patients with a control group which was composed of 213 patients, the results showed that patients with NAFLD were had higher incidence of carotid atherosclerosis plaque than the control group, and there was a remarkable correlation between NAFLD and carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature data describes that some factors should be considered risk predictors for the occurrence of SAH, among them are obstructive sleep apnea syndrome, body mass index (BMI), waist circumference (WC), abdominal visceral fat, heart rate variability (8)(9)(10), some laboratory biochemical markers and associated comorbidities (11)(12)(13). Due to the number of variables and their possible associations, further research on relationships between these data and SAH is necessary, so that more reliable and independent predictors can be obtained for decision making in clinical practice, facilitating the prognostic of SAH in this population.…”
Section: Introductionmentioning
confidence: 99%